Finite Element Analysis of Cannulated Screws as Prophylactic Intervention of Hip Fractures. (18th November 2021) - Rhee, Brian; Tommasini, Steven M.; Milligan, Kenneth; Moulton, Julia; Leslie, Michael; Wiznia, Daniel H.
Introduction: The frequency of hip fractures, a major cause of morbidity and mortality for geriatric patients, is expected to increase exponentially in the next few decades. The aim of this study is to assess the ability of stainless-steel cannulated screws to reduce the risk of a femoral neck fracture, if placed prophylactically prior to a fall. Materials and Methods: We created finite element models from computed tomography (CT) scan-based 3D models of a geriatric patient through 3D-image processing and model generation software. We used linear finite element simulations to analyze the effect of cannulated screws in the proximal femur in single-leg stance and lateral fall, which were processed for peak von Mises stresses and element failure. Findings: Prophylactically placed cannulated screws significantly reduced failure in an osteoporotic proximal femur undergoing lateral fall. Three implanted screws in an inverted triangle formation decreased proximal femoral trabecular failure by 21% and cortical failure by 5%. This reduction in failure was achieved with a 55% decrease in femoral neck failure and 14% in lateral cortex failure. Conclusion: Our results indicate that cannulated hip screws in an inverted triangle formation may strengthen an osteoporotic proximal femur in the event of a lateral fall. Mechanical testing on cadaveric or composite models is required to validate these results.